PENGARUH PEMBERIAN KOMPOS DAUN BAMBU TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea canephora) PADA TANAH GAMBUT - wawan, wawan; Rosmalinda, Rosmalinda; Sopiana, Sopiana (Journal of Agro Plantation (JAP), 2024)
Coffee cultivation cannot be separated from the seeding media, one of which is the media, one of which is peat which is widespread in Indonesia, the limited nutrient elements of peat are overcome by providing bamboo leaf compost, containing 1.35% N, 3.47% P, 0.37% K. The research aims to determine the effect of providing bamboo leaf compost on the growth of robusta coffee seedlings in peat soil. The research was conducted at the Sungai Awan Kiri Village Experimental Garden, Muara Pawan District, from March to June 2024. The research used a completely randomized design (CRD) consisting of 5 treatments and 5 replications, there were 25 experimental units, each experiment consisted of 3 samples so that the total number was 75 samples. . The parameters observed were plant height, stem diameter, number of leaves, root length and wet weight. The data was analyzed statistically using Analysis of Variance (ANOVA), if what was found had a real effect, then continued with the Duncan Multi Range Test (DMRT) at the 5% level. The results showed that the application of bamboo leaf compost had a real influence on the growth of Robusta coffee seedlings on plant height, stem diameter, number of leaves, root length and plant fresh weight. A dose of bamboo leaf compost of 450 g/polybag was the best treatment to increase the growth of robusta coffee seedlings with an average seedling height of 10.35 cm, stem diameter of 2.73 mm, number of leaves of 9.47, root length of 12.62 cm and plant wet weight of 2.59 g.